ANALISIS KREATIVITAS DAN INOVASI PRODUK DALAM MENINGKATKAN DAYA SAING PADA TISYA BAKERY SUNGAI BAHAR - Anti Widiyani; Anzu Elvia Zahara (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to determine the implementation of product creativity, competitiveness, and obstacles faced by Tisya Bakery. The study used a descriptive qualitative approach with three main informants: the owner, employees, and customers. Data were collected through observation, documentation, and interviews, then analyzed using data reduction, data presentation, and verification. The results of the study indicate that product creativity at Tisya Bakery is still limited, with a lack of innovation and distinctive characteristics that differentiate products from competitors. The use of social media for marketing is also still minimal, resulting in limited market reach. To increase competitiveness, Tisya Bakery needs to develop creative and unique products, improve the quality of raw materials, improve packaging design, and optimize the use of digital platforms. In addition, improving service and product quality consistency is crucial to maintain customer loyalty. The study recommends diverse product innovations, active use of social media, employee training in service, and collaboration with local businesses to expand distribution. With these creative and innovative strategies, Tisya Bakery is expected to increase its competitiveness and become the primary choice for the Sungai Bahar community. Keywords: Product Creativity, Competitiveness, Innovation, Marketing Strateg